The Connectors: How the World's Most Successful Businesspeople Build Relationships and Win Clients for Life - Maribeth Kuzmeski (Wiley, 2011)
In today's commoditized marketplace, no matter what product or service you sell, there's probably someone somewhere able to offer it cheaper, faster, and maybe even better. So how do you differentiate yourself from your competitors? The Connectors shows that the only thing that truly sets you apart is the quality of your relationships with your clients and customers.